Evaluating the stock status of Trachurus trecae (Cadenat, 1950) in the Eastern Central Atlantic Ocean based on an extended surplus production model incorporating life history and fishery selectivity - Komba Jossie Konoyima (Journal of Marine Studies, 2025)
This study on Trachurus trachurus used data from the Regional Committee (CECAF). It employs JABBA-Select, a model that balances age-structured and traditional surplus production models, uniquely incorporating life history and fishery selectivity. Sensitivity scenarios included single and combined catch per unit effort (CPUE) data (1999-2017) for demersal and pelagic fisheries under logistic and dome-shaped selectivity functions. Results indicated that the demersal CPUE under logistic selectivity performed best, leading to a single-fleet analysis as the base case. Model results were robust against variations in natural mortality (M) compared to other input parameters, including steepness (h), while stock status perceptions remained consistent. The base case revealed an overexploited stock (SB/SBMSY = 66%) with a slow growth rate (r = 29%) in 2017. Catches exceeding 15,744 tons from 2022 to 2030 may not be sustainable. JABBA-Select is recommended for future assessments; however, careful consideration of input parameters is essential to minimize uncertainties.